Effects of branched-chain amino acids on the muscle–brain metabolic axis: enhancing energy metabolism and neurological functions, and endurance exercise in aging-related conditions - Wu, Jing (Frontiers in Nutrition, 2025)
Aging is related to a decline in muscle mass, cognitive capabilities, and exercise proficiency, all of which collectively diminish quality of life and heighten the susceptibility to chronic illnesses. Branched-chain amino acids (BCAAs), with specific emphasis on leucine, have surfaced as pivotal regulators of muscle metabolism and may significantly influence the muscle–brain metabolic axis, thereby affecting hippocampal plasticity and cognitive wellbeing. This review consolidates contemporary evidence from 21 clinical and experimental investigations examining the influences of BCAA intake in conjunction with exercise on muscle functionality, cognitive outcomes, and endurance capacity in conditions associated with aging. The results indicate that BCAA supplementation, particularly when augmented with leucine and combined with resistance or multicomponent exercise regimens, facilitates muscle protein synthesis, mitigates inflammation, and enhances physical performance in the elderly population. Initial data also suggest possible advantages for hippocampal plasticity and cognitive function; however, this domain necessitates further investigation. The presence of challenges such as variability in study methodologies, supplementation regimens, and demographic characteristics of participants constrains the ability to draw definitive conclusions. Subsequent research endeavors ought to concentrate on clarifying the mechanistic pathways that connect muscular and cognitive health, refining supplementation methodologies, and investigating tailored strategies to alleviate age-associated sarcopenia and cognitive deterioration. In summary, the combination of BCAAs with physical exercise presents a potentially effective intervention to facilitate healthy aging through the interconnected metabolic axis of muscle and brain.